Conservation Tourism - Buckley, Ralf (CABI, 2014)
Conservation of biological diversity and functioning ecosystems is critical for human well-being; yet it is increasingly threatened through continuing population growth, consumption and contamination of natural resources and ecosystems, and now also by climate change. The global protected area network has made enormous contributions to conservation, but it is not enough on its own and it also is under continual threat. Additional social and economic mechanisms are urgently needed to support the public reserve system and extend conservation efforts outside reserves. Conservation tourism is one component, small as yet but potentially signifcant. Tourism is a multi-trillion dollar global industry with major economic, social and environmental impacts. In common with most industry sectors, most of its environmental impacts are harmful or negative. Indeed, since a large component of the industry takes tourists specifcally to areas of high conservation value (Buckley et al., 2003a), these impacts are of particular ecological signifcance (Buckley, 2004a). Unlike most other sectors, however, commercial tourism can on occasion make net positive contributions to conservation. These can operate either directly, or indirectly through local communities and national or international politics. Some of these ventures are marketed as ecotourism and are listed in global compendia of ecotourism case studies (Buckley, 2003a; Zeppel, 2006). This volume builds on previous research by assembling and analysing examples where commercial tourism has indeed contributed to conservation. This is a feld where reliable information is hard to come by. Many tourism operations claim environmental credentials, but most of these evaporate under closer scrutiny, even where they have received environmental certifcation or awards. This volume therefore focuses largely on cases where respected international researchers have made extended on-site investigations. Recognizing that ecosystems, societies, economies and laws differ considerably between countries and continents, most of these cases are presented in geographical order, in an attempt to examine regional signatures in conservation tourism efforts. In addition, to illustrate what can be achieved by companies seriously involved in conservation tourism, four individual enterprises with particularly well-established credentials are frst profled in more depth.